Long-term intermittent pharmacological therapy of uterine fibroids – a possibility to avoid hysterectomy and its negative consequences - Olejek, Anita; Olszak-Wąsik, Katarzyna; Czerwinska-Bednarska, Anna (Menopause Review/Przegląd Menopauzalny, 2016)
Uterine fibroids are found in almost 20-40% of women of reproductive age. For each woman an individualised treatment method should be applied because the hysterectomy procedure is not a good option in every case. The uterus is an organ necessary not only in reproduction. Its removal may result in: pelvic floor dysfunction and stress urinary incontinence, negative impair on life quality, depressive disorders, increased risk of cardiovascular and neurodegenerative diseases, and higher incidence of neoplastic disease. According to the last scientific reports, selective progesterone receptor modulators are the effective therapeutic option in uterine fibroids in women of reproductive age because progesterone is an important factor in their pathogenesis. Ulipristal acetate (UPA) is a progesterone receptor antagonist. It inhibits cell proliferation and angiogenesis in uterine fibroids and also reduces collagen deposits in extracellular matrix. Significant data concerning ulipristal acetate efficacy have been provided by scientific research, especially from the consecutive PEARL studies. Oral ulipristal acetate effectively and safely controls bleeding and pain in patients with symptomatic fibroids. It reduces fibroid volume and restores quality of life. The results of UPA long-term intermittent treatment are largely maintained during the off-treatment periods.